Characterisation of Roman Mortar from the Archaeological Site of Mirobriga - Chua, Alvin (2020)
Mirobriga is a Roman site located in the municipality of Santiago do Cacém, in Setúbal, a district in the southwest of Portugal. Mortar samples were collected from the domestic, commercial buildings, and public buildings from the site. The samples may be divided according to their function – filling, rendering, and plaster. The chemical, mineralogical, and microstructural characterisation of the samples was performed using a number of complementary techniques – stereomicroscopy, polarised light microscopy, chemical and granulometric analysis, thermogravimetric analysis (TGA), powder X-ray diffraction (XRD), and variable pressure scanning electron microscopy-energy dispersive spectrometry (SEM-EDS). The results show that in most of the samples, the aggregates consist of quartz sand, whilst the binder is lime-based. The exception, however, may be seen in the samples where stratigraphy is present. In such samples, the external layer of the mortar functions as a plaster, and both the aggregate and the binder consist of calcite. In addition, the majority of samples have a binder to aggregate ratio of 1 : 3. As a whole, the raw materials used for the production of the mortars may be said to be quite similar, and shows little difference between the filling and rendering mortars, though the aggregates of these two types of mortar are different from those functioning as plaster.